HOM Videos, ep. 10 Mimetic Trouble with Judith Butler: I. Gender Trouble Revisited - Butler, Judith (HOM Videos ERC Project Homo Mimeticus, 2025)
In this last dialogue for HOM Videos, Nidesh Lawtoo meets Judith Butler in Paris to account for the role a different, psychic, performative and troubling conception of mimesis play in their influential work. Taking a genealogical approach to Butler's latest book to date, Who Is Afraid of Gender, Lawtoo asks Butler to revisit the role mimetic and expressive theories of aesthetic play in their influential book, Gender Trouble (I). As the dialogue unfolds, they consider the role of "psychic mimesis" (II) in opening up a relational conception of subjectivity that paves the way for Butler's work on grief and non-violence (III), giving an account of self in relation to others (IV) in order to re-turn to the phantasm of gender mobilized by (new) fascist leaders in the present.